Local vacuum electron beam welding for pressure vessel applications. (November 2015) - Lawler, S.; Clark, D.; Punshon, C.; Bagshaw, N.; Disney, C.; Powers, J.
Abstract : Welding of thick section components such as pressure vessels used in the nuclear industry is traditionally performed using arc welding techniques, requiring multiple weld passes, with interstage non-destructive examination (NDE) and preheating of the component to reduce the risk of hydrogen cracking. Electron beam (EB) welding offers the opportunity to weld thick section components in a single pass and negates the need for interstage NDE, resulting in saving significant time and cost in the fabrication of nuclear vessels. Furthermore, elimination of the preheat step may be possible since the EB process is carried out in a vacuum environment. However, due to the physical size and geometry of nuclear vessels, traditional vacuum chambers would be prohibitively expensive when considering the low volume of output in the nuclear industry. Rolls-Royce and TWI are working on a local vacuum, or 'out of chamber', EB welding system, which eliminates the need of such a vacuum chamber and brings the vacuum to the component, thus making EB welding of nuclear vessels more practical and financially viable.